P031 Use of disodium etidronate and sodium thiosulfate in a premature neonate with generalised arterial calcification of infancy. Issue 7 (19th June 2019) - Hollwey, Alexandra; Forster, Chris; Mushtaq, Talat
Abstract : Situation: A 30 week gestation male weighing 1.66kg presented with metabolic acidosis and high lactate and subsequently developed heart failure and hypertension. He initially started enteral feeds but these were later not tolerated and TPN commenced. On day 8 calcification of the aorta was identified on echocardiogram. CT scans showed extensive arterial calcification including the thoracic and abdominal aorta, subclavian and common carotid arteries, coeliac axis, SMA, renal arteries and iliac vessels. Generalised arterial calcification of infancy (GACI) due to ENPP1 mutation was suspected. Background: GACI, a rare autosomal recessive condition can be caused by ENPP1 mutation leading to low levels of inorganic pyrophosphate (PPi), a negative regulator of calcification. GACI has a high mortality rate, up to 55% at 6 months. Mortality has been shown to improve in those who survive the first few months of life. 1 Treatment: Intravenous sodium thiosulfate, licensed for cyanide poisoning and used off-label for calciphylaxis in adults, 2 was commenced to try and reduce existing calcification. Dosing that has been known to be used in three other babies from two different centres, 3 was used - 12.5g/m 2 over 30minutes on alternate days for 2 weeks followed by 12.5g/m 2 five days a week. This is in the same scale as adult calciphylaxis dosing and up to 400mg/kg can be used in paediatric cyanide poisoning. Bisphosphonates were commenced to prevent further calcification. Etidronate, a non-nitrogen containing bisphosphonate, was preferred due to its closer structural similarity to PPi than second generation bisphosphonates. Etidronate has been discontinued in the UK so was not initially available and a dose of pamidronate was given. A Canadian import of etidronate was sourced and commenced a week later. Due to SMA and coeliac axis calcification there were concerns regarding bowel perfusion and he was TPN fed except for 20ml/kg/day EBM. Etidronate 20mg/kg/day was commenced in three divided doses to improve gastrointestinal tolerance. Outcome: Initially his heart failure stabilised and hypertension managed with carvedilol. By day 35 full enteral feeds were reached and he was breathing unassisted in air. CT after one month's treatment showed no worsening of vascular calcification, though unfortunately calcification did not appear to have improved. At 7 weeks he became tachypnoeic due to worsening heart failure and required respiratory support. Despite ongoing medical therapies he passed away at 8 weeks of age. Challenges and lessons learnt: Due to the rarity of the condition information on treatment options, dosing and monitoring are limited and the need to use an imported product lead to a short delay in treatment. Etidronate is only available in tablet form but Didronel brand can be crushed and suspended in water, 4 Information about the suspension's uniformity is unavailable but due to a lack of alternatives this was the option taken. A two hour break either side of etidronate while recommended, was compromised to ninety minutes as he required three hourly feeds. Combination treatment was used to try to reduce the calcification; however the extent of calcification had already caused significant cardiac compromise which ultimately led to his demise. References: Ferreira C, Ziegler S, Gahl WA. Generalized Arterial Calcification of Infancy. 2014 In: Adam MP, Ardinger HH, Pagon RA, et al ., editors. GeneReviews [Online]. Seattle (WA): University of Washington, Seattle; 1993–2018. Available from: https://www.ncbi.nlm.nih.gov/books/NBK253403 Nigwekar SU, Brunelli SM, Meade D, et al. Sodium thiosulfate therapy for calcific uremic arteriolopathy. Clin J Am Soc Nephrol, 2013;8:1162–70. Personal communication: Medicines Information, Alder Hey Children's NHS Foundation Trust . Email sent to: Leeds Medicines Advisory Service. 28th June 2018. White R, Bradnam V. Handbook of Drug Administration via Enteral Feeding Tubes, Third ed. Cornwall: Pharmaceutical Press; 2015. www.medicinescomplete.com (accessed August 2018).